Research Methods and Techniques in Architecture, 1st edition - Elzbieta Danuta, Niezabitowska (Routledge, 2020)
A scientific approach to architectural and architectonic research from the scope of just one discipline is no longer sufficient. With contemporary considerations such as behavior, health, and environmental protection, architects and students alike need holistic research methodologies that incorporate qualitative elements as well as more traditional quantitative ones. Research Methods and Techniques in Architecture examines research methodologies and tools applied in science and architectonic practice. Beginning with a thorough introduction to the main scientific, environmental, and architectural theories of the late twentieth century, the book guides the reader through the different aspects of architectural research design, building research teams, choosing applicable research methods, and representing research results.